2011
DOI: 10.3390/molecules16075682
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anticancer Activity of Some New S-Glycosyl and S-Alkyl 1,2,4-Triazinone Derivatives

Abstract: A series of S-glycosyl and S-alkyl derivatives of 4-amino-3-mercapto-6-(2-(2-thienyl)vinyl)-1,2,4-triazin-5(4H)-one (1)were synthesized using different halo compounds such as preacetylated sugar bromide, 4-bromobutylacetate, 2-acetoxyethoxy-methyl bromide, 3-chloropropanol, 1,3-dichloro-2-propanol, epichlorohydrin, allyl bromide, propargyl bromide, phthalic and succinic acids in POCl3. The structures of the synthesized compounds have been deduced from their elemental analysis and spectral (IR, 1H-NMR, and 13C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…Several glycosides have exhibited potent activity as biological inhibitors [29][30][31][32][33][34][35][36], inducers and ligands [37], in addition to having excellent chemoselectivity in glycosylation processes as donors and acceptors [38]. Keeping this context in mind, as a continuation of our previous work on the synthesis of glycosides with biological activity [39], we targeted a group of pyridine compounds functionalized with cyano group and pyridine and p-isopropylphenyl rings. The anticancer and antimicrobial activities of the newly synthesized compounds have been examined to examine whether the presence of glycosyl residues enhances their biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Several glycosides have exhibited potent activity as biological inhibitors [29][30][31][32][33][34][35][36], inducers and ligands [37], in addition to having excellent chemoselectivity in glycosylation processes as donors and acceptors [38]. Keeping this context in mind, as a continuation of our previous work on the synthesis of glycosides with biological activity [39], we targeted a group of pyridine compounds functionalized with cyano group and pyridine and p-isopropylphenyl rings. The anticancer and antimicrobial activities of the newly synthesized compounds have been examined to examine whether the presence of glycosyl residues enhances their biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…A literature survey showed that coupling of heterocyclic thiones with epichlorohydrin as an electrophile may give oxiranylmethylsulfanyloxadiazoles by keeping the oxiran ring as it is or cleaving the oxiran ring to yield a 3‐chloro‐2‐hydroxyprop‐1‐ylsulfanyl‐heterocycle .…”
Section: Resultsmentioning
confidence: 99%
“…6-Aza analogues of the naturally occurring nucleic acids components represent isosteres with the C-6 carbon atom of the pyrimidine nucleoside base being replaced by nitrogen. 7,8 Certain azanucleosides, 6-azauracil and 6-azacytosine), structurally based on 1,2,4-triazine nucleus have displayed an impressive array of biological activities, among which antitumor, [9][10][11][12][13][14][15][16][17][18][19] antiviral, 20 antimicrobial, 21 antiinflammatory, 22 antiplatelet, 23 antimalarial, 24 and antifungal 25 properties. Additionally, tertiary amines in the linkers reported to be positively charged at physiological pH in order to favor electrostatic interactions in the minor groove with the anionic phosphate DNA backbone.…”
Section: Introductionmentioning
confidence: 99%